Diagnostic Accuracy of Hepatic Vein Resistive Index in Detection of Hepatic Fibrosis in Patients of Chronic Liver Disease - Sidrah Nadeem , Sana Wasim , Sidrah Manzoor , Hareem Ata , Riffat Raja , Sadaf Arooj, Sidrah Nadeem , Sana Wasim , Sidrah Manzoor , Hareem Ata , Riffat Raja , Sadaf Arooj (Journal of Rawalpindi Medical College, 2020)
Introduction: If we could prove the diagnostic accuracy of hepatic vein resistive index in detecting liver fibrosis in chronic liver disease patients, this would be beneficial for the patients as it is a non-invasive, readily available, and cost-effective technique for the diagnosis of liver fibrosis. This will help the physicians in the early initiation of definitive management. Materials and Methods: Seventy-five (n=75) patients with hepatitis B aged between 18-50 years were enrolled. Hepatic vein resistive index and liver biopsy were performed in even-patients. Sensitivity, Specificity, PPV, NPV, and overall accuracy of the hepatic vein resistive index was calculated. Results: Average age group studied was 38y ± 8.2 SD. 57.3 % (N=43) were males and 42.7% (n=32) patients were females respectively. Data of this work Exhibits various statistical indicators 77%. 96.7%. 97.2%. 74.3% and 85.3% respectively. Conclusion: Hepatic vein resistive index measured by ultrasonography can detect liver fibrosis in CLD with overall sensitivity, Specificity, PPV, NPV, and accuracy of 77.7%. 96.7%. 97.2%. 74.3% and 85.3% respectively.